On rings with weakly prime centers - Junchao Wei (Український математичний журнал, 2014)
We introduce a class of rings obtained as a generalization of rings with prime centers. A ring R is called weakly prime center (or simply WPC) if ab∈Z(R) (R) implies that aRb is an ideal of R where Z(R) stands for the center of R. The structure and properties of these rings are studied and the relationships between prime center rings, strongly regular rings, and WPC rings are discussed, parallel with the relationship between the WPC and commutativity. Введено клас кілєць, що є узагальненням кілєць з простими центрами. Кільце R називається слабко простим центром (чи просто WPC), якщо з включення ab∈Z(R) випливає, що aRb є ідеалом R, де Z(R) — центр R. Вивчено структуру i властивості таких кілець та проаналізовано співвідношення між простими центральними кільцями, сильно регулярними кільцями та кільцями з слабко простим центром паралельно зі співвідношенням між слабко простим центром та комутативністю.